Distribution and Suitable Habitat of the Cold-Water Corals Lophelia pertusa, Paragorgia arborea, and Primnoa resedaeformis on the Norwegian Continental Shelf - Sundahl, Hanna; Buhl-Mortensen, Pål; Buhl-Mortensen, Lene (Frontiers in Marine Science, 2020)
Cold-water corals are habitat-forming species that are also classified as indicators of Vulnerable Marine Ecosystems (VMEs) due to the threat of various anthropogenic impacts e.g. fisheries and oil/mineral exploration. To best protect VMEs, knowledge of their habitat requirements and distribution is essential. However, comprehensive sampling of the deep sea is difficult due to access and cost constraints, so species distribution modeling (SDM) is often used to predict overall distributions and ecological preferences of species based on limited data. We used Maximum Entropy (Maxent) modeling to predict the probability of presence of the reef-building scleractinian Lophelia pertusa and the octocorals Paragorgia arborea and Primnoa resedaeformis using a total of 2149 coral presence points and 15 environmental predictor variables. The environmental variables used in the analysis were processed to 176m resolution and included bathymetry, depth, geomorphometric characteristics (slope, aspect and bathymetric position index (BPI)), oceanography (temperature, salinity, current directions and speed), surface chlorophyll a concentration, sediment type, and marine landscape type. Comparing presence points with environmental data showed that the temperature and depth range for Lophelia was narrower compared to the gorgonians, and it occurred in shallower, warmer water. Observations showed that Lophelia had a broad, bimodal response to Broad BPI, while the predicted model indicated a more narrow response. Paragorgia tolerated the greatest range of sloping according to the model. All three species were observed with a bimodal pattern along a wide range of mean current speed, while the models indicated a high response to faster current speed. Jackknife tests showed that sediment type was an important predictor for gorgonian corals, while BPI and minimum temperature were more important for Lophelia. The spatial precision of the models could be further increased by applying environmental layers with a higher and uniform spatial resolution. The predicted distribution of corals and their relation to environmental variables provides an important background for prioritizing areas for detailed mapping surveys and will aid in the conservation efforts for these VMEs in Norwegian waters and beyond.